EXPLAINING THE TOURISM RELATIONSHIP MANAGEMENT (TRM) IN TOURISM ENTERPRISES (CASE STUDY: ISFAHAN) - Farahani, Maryam Ghiasabadi; Gheshlagh, Siavash Imeni; Sarfi, Alireza (ASEAN Marketing Journal, 2021)
Manuscript type: Research paper Research Aims: The aim of the present study is to explain the relationship management with tourism in Isfahan tourism enterprises using structural equation modeling methodology. Design/methodology/approach: Based on distributing 312 questionnaires, the sample size was 300 academic experts, specialists and experts working in Isfahan tourism enterprises and professors and tourists in the fields of tourism management, IT and marketing selected by combining non-probability purposive (judgmental) sampling and snowball sampling methods. Research Findings: The results showed a correlation between “applications of TRM system” and “users' satisfaction with TRM” based on path analysis concerning confirmatory factor loadings analysis as 0.566 and a correlation between “applications of TRM system” and “IMHTs” based on path analysis concerning confirmatory factor loadings analysis as 0.521. Moreover, there was a correlation between “Consumers' satisfaction with TRM” and “IMHTs” based on path analysis concerning confirmatory factor loadings analysis as 0.936. Theoretical Contribution/Originality: The conceptual model of the study involves components including “the applications of TRM system,” “satisfaction of the tourists with TRM,” and “information management of health tourists (IMHTs)”. Practitioner/Policy Implication: 1) the analysis of information of health professionals, 2) converting information of health professionals, 3) retrieving information from health professionals, strategic attention in organizational decisions in tourism enterprises of Isfahan because the general manager of cultural heritage, tourism and handicrafts of Isfahan from holding the first quarterly meeting to review the tourism situation in Isfahan in 2021 entitled “path recognition” with the presence of young and elite tourism activists and announced to create futuristic thinking and the need for elite thinking in the future of Isfahan. Research limitation/Implications: The tourism industry of Isfahan is currently so important in the comprehensive development of countries that economists call it invisible exports, and it is one of the largest industries in the world today.